2017
DOI: 10.1101/232066
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Probing cellular response to topography in three dimensions

Abstract: Biophysical aspects of in vivo tissue microenvironments include microscale mechanical properties, fibrillar alignment, architecture or topography of the extracellular matrix (ECM), and the repertoire of ECM ligands present, all of which provide cues to drive cellular response. Cell-ECM interactions are important regulators of both normal tissue homeostasis and malignancy.Thus, understanding both extracellular cues and the cellular responses they elicit is fundamental to developing therapeutic strategies. Vario… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 79 publications
(77 reference statements)
0
12
0
Order By: Relevance
“…Histologically, abnormal remodeling of collagen mainly results in excessive deposition, altered-proportions and changed-arrangement of collagen ( 10 12 ). In normal tissues, the collagen fibers of the tumor matrix are curly with an irregular arrangement, while in tumor tissues, especially those with metastasis, the fibers are linearized and dense with a directional arrangement ( 13 ). Tanjore and Kalluri ( 14 ) identified numerous hidden carcinogen-containing domains within collagen that were exposed following collagen remodeling, and which subsequently facilitated tumor metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Histologically, abnormal remodeling of collagen mainly results in excessive deposition, altered-proportions and changed-arrangement of collagen ( 10 12 ). In normal tissues, the collagen fibers of the tumor matrix are curly with an irregular arrangement, while in tumor tissues, especially those with metastasis, the fibers are linearized and dense with a directional arrangement ( 13 ). Tanjore and Kalluri ( 14 ) identified numerous hidden carcinogen-containing domains within collagen that were exposed following collagen remodeling, and which subsequently facilitated tumor metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, functionally blocking antibodies against integrins that mainly bind to laminin inhibits tube formation, while blocking other integrins has no significant effect. While laminin gels are per se amorphous, it has been shown that cell-sized fibrous structures can be induced by mechanical forces, like the external application of fluid flow (33) or exerting a force via paramagnetic particles in a magnetic field (34). Here, we observe that Matrigel is rearranged into fibres by the exposure to cells.…”
Section: Discussionmentioning
confidence: 99%
“…Such "designer biomaterials" may permit improved control over distinct mechanical and biochemical features of the cell microenvironment. For example, aligned ECM cues can be patterned within a homogeneous matrix using magnetic nanoparticle self-assembly, allowing for hydrogels with modulated alignment cues while maintaining comparable elastic moduli and ligand densities 123,124 .…”
Section: The Extracellular Matrix and Engineered Biomaterialsmentioning
confidence: 99%